Accessibility and affordability of higher education institutions in Davao region a spatial distribution analysis - Bibay, Darryl B.
The study seeks to address the concern of students on the accessibility of higher education institutions and concern of families on the overall affordability of higher education. Its objective is to determine the accessibility and affordability of higher education institutions in Davao Region. The study employs the descriptive and historical methods of research. It also uses the historical method. The following findings were obtained: 1. HEIs in the region are relatively close to prospective college students. 2. There are sufficient numbers of HEIs in the region. 3. HEIs are concentrated in growth centers in the region. 4. The total cost of tertiary education per year per student is roughly estimated at P76.535.49. 5. There is a significant positive relationship of accessibility of HEIs to the level of participation of the students in tertiary education. 6. There is also a significant positive effect of affordability of HEIs to the level of participation of students in tertiary education. As policy recommendations, the study proposes the following: 1. There is a need to rationalize the accreditation and location of HEIs in the region. 2. There might be a need to "socialize" the rate of tuition fees and the total cost of education. In terms of research recommendations, the study proposes the conduct of the following related studies: 1. Analysis of course offerings of HEIs versus demands and requirements of industries in the region. 2. In-depth analysis of social, economic and residential origins of students in HEIs in the region. 3. Analysis of competitiveness and capacity of HEIs in the region. 4. Determination and analysis of support facilities of tertiary education. 5. Extent of movement and mobility of students for tertiary education.
Thesis, Graduate (MA Urban and Regional Planning)--UP in Mindanao.
Keywords: Education, Higher -- Davao region (Philippines)